Pemberdayaan Ibu Kader PKK dalam Upaya Pencegahan Stunting di Desa Sari Gadung Kabupaten Tanah Bumbu Kalimantan Selatan: Family Welfare Building in the Prevention of Stunting in Sari Gadung Village, Bumbu Kalimantan South Land District - Wati, Helmina; Muthia, Rahmi; Prihandini, Yustin Ari; Santoso, Untung; Soedarwo, Vina Salviana Darvina; Nursandi, Fatimah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
In South Kalimantan, the stunting incidence rate in 2022 will be 24.6%, more significant than the national prevalence rate of 21.6%. Tanah Bumbu is one of the districts located in South Kalimantan Province, with the incidence of stunting in Tanah Bumbu district, according to SSGI data, reaching 16.1%. Sari Gadung Village is one of the villages in Simpang Empat District, Tanah Spice Regency. This village has a potentially productive group, namely Posyandu Cadres. Data on the incidence of stunting in Tanah Spice Regency reached 16.1%. Providing health supplements to the community is needed to improve community health in Sari Gadung village and prevent stunting. This community service activity aims to prevent stunting by providing health checks, including checking Hb, glucose, uric acid, and blood pressure, and providing blood supplements. The method is that adult female patients are given drug information regarding the use of iron and folic acid drugs, and then their Hb, glucose, uric acid, and blood pressure are checked. The results of this activity showed that the number of patients who took part in the activity was 37, the average Hb value was 15.9 g/dL, the average uric acid was 8.6 mg/dL, the mean glucose was 112.5 mg/dL, and the blood pressure was 122/82 mmHg. The conclusion is that the results of the health examination at the posyandu in Sari Gadung village are still in the normal category.